Obtaining and study of physical-chemical properties of porous materials based on kaolin - Bondarieva, Antonina; Tobilko, Viktoriia (Technology audit and production reserves, 2023)
The object of research is kaolin from the Hlukhovetsky deposit (Ukraine). On its basis, granulated sorbent materials were obtained with the addition of various amounts of cellulose as a pore former. After forming the samples, they were dried and fired at a temperature of 800 °C. The obtained granules with a size of 8–9 mm were modified with zero-valent iron. The physicochemical, including sorption properties of granular composites were studied. Using scanning electron microscopy (SEM) with energy dispersive X-ray spectroscopy (EDS), the morphology of the obtained samples was investigated and the presence of zero-valent iron particles on the surface and in the pores of the sorbents was confirmed. Based on desorption experiments, it was determined by chemical analysis that the Fe0 content in modified samples with increased pore former content increases from 0.01 g/g of granules for a sample containing 1% cellulose to 0.016 g/g for a carrier with 3 % pore former. The specific surface area and pore volume of the samples were determined by the method of low-temperature adsorption-desorption of nitrogen. Thus, with an increase in the content of the pore former in the ceramic mass, the specific surface of both unmodified and modified samples slightly decreases. Thus, with a cellulose content of 1 %, it is 20 m2/g and 17 m2/g, respectively. When the pore former is increased to 3%, these values are 15 m2/g and 12 m2/g. After applying a layer of zero-valent iron on porous granules, the volume of pores decreases, which is due to the formation of agglomerates of iron particles during synthesis. The study of the sorption capacity of the obtained sorbents with respect to Cr(VI) from model solutions containing a mixture of metal cations (copper, cadmium, cobalt, zinc) showed that granular materials exhibit sorption capacity for metal anions, even in the presence of cations. The amount of chromium sorption naturally increases for modified samples with an increase in the cellulose content in them. However, for model solutions that do not additionally contain metal cations, the sorption value is somewhat higher. Thus, for a sample with a 3 % pore former content, the sorption value is 0.7 mg/g and 0.9 mg/g, respectively, at an initial chromium(VI) concentration of 10 mg/g. The obtained experimental data indicate that the obtained porous granular sorbents based on kaolin can be used in the further treatment of wastewater from electroplating enterprises, which contain a mixture of pollutants in both anionic and cationic forms.